Perancangan Web Design Aplikasi E-Learning dengan Metode Prototype pada Tingkat SMA - Frederica Rosabel Ramli; Fikri Hakim; Ria Anggelina Hutabarat (Universitas Putra Indonesia YPTK Padang, 2021)
Technology has experienced very rapid development at this time and has brought changes and has a positive and negative impact on human life. One of the fields currently contaminated by technological developments is the field of education, especially in Indonesia, where at first the learning system was still manual-based and is currently developing into an online learning system. It is clear that various levels of schools and universities have used technology to support their learning process and apply it. One of the uses of technology in the field of education is learning management systems (NGOs) such as e-learning. The use of e-learning as a learning medium has a function to improve the quality of student learning and help improve student understanding in learning. However, there are still many schools that have not implemented e-learning in their teaching and learning process, such as high school (SMA). Therefore, the design of this e-learning application web design is expected to help several schools that require an online learning system that is user friendly so that schools can be better prepared to follow current development trends.